NUTRITION FULFILLMENT IN ADOLESCENTS: BEWARE OF OBESITY - Riesmiyatiningdyah Riesmiyatiningdyah; Kusuma Wijaya Ridi Putra; Agus Sulistyowati; Muniroh Muniroh; Susila Nur Islami; Risa Dwi Prianti; Ashley Syahira (Community Service Journal of Indonesia, 2022)
Health counseling activities given to adolescents about Obesity at the Islamic Boarding School of Tahfidz Putri Hidayatullah, Sidoarjo are a form of community service in the form of counseling aimed at the knowledge of young girls who are at the Islamic Boarding School of Tahfidz Putri Hidayatullah, Sidoarjo about obesity in order to welcome Children's Nutrition Day so that these young women are able to increase their knowledge related to the fulfillment of balanced nutrition according to the needs of their bodies. The activity will be held on January 28, 2022, at the Islamic Boarding School of Tahfidz Putri Hidayatullah, Sidoarjo. With the target is the young women who are in the Islamic Boarding School of Tahfidz Putri Hidayatullah, Sidoarjo. Prior to the implementation of these activities, there is a process of preparing activities for approximately 3 weeks before the activities are carried out, starting from determining the theme of the extension to applying for permits to the relevant parties. As a form of evaluation, the activity was attended by 30 young women, participants participated in the activity with great enthusiasm, health promotion activities could run on time and smoothly.